THE CORRELATION BETWEEN ANTENATAL CARE (ANC) REGULAR VISIT AND ANAEMIA CASE OF PREGNANT WOMEN IN THE THIRD TRIMESTER IN TANJUNG KARANG HEALTH CENTER MATARAM - Liza nurul khawatib (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2020)
Antenatal Care treatment is an examination to optimize phsycal and mental health of pregnant women in order to be able to face birth delivery, postnatal condition, providing breast milk, and the retrieval of reproduction heath condition normally. Now pregnant women still face anaemia. This research is aimed at identifying the correlation between Antenatal Care regular visit and anaemia case of pregnant women in third trimester in Tanjung Karang Health Center Mataram. This research is designed as descriptive analytic study with Cross-Sectional approach. The samples was were 32 selected through purposive sampling from 46 populations pf pregnant women in third trimester . the instrument to the measure the variables is registry book in April 2019 and the data analyzed using Chi-Square with level of significance of 5%. The research showed that 81,2% of pregnant women has the regular Antenatal Care visit. 11,5% had anaemia. Of 88,5% women that had no anaemia. 66,7% had no regular visit of Antetanatal Care. There is correlation between Antenatal Care regular visit to health center and anaemia case of pregnant women in third trimester in Tanjung Karang Health Center Mataram p=0,003. The more regular the antenatal visit, the less risk of anaemia is. Pregnant women should be more actively and regularly visit health center to avoid anaemia